An electro-mobility system for freight service in urban areas. (2015) - Molfino, Rezia; Zoppi, Matteo; Muscolo, Giovanni Gerardo; Cepolina, Elvezia M.; Farina, Alessandro; Nashashibi, Fawzi; Pollard, Evangeline; Dominguez, José Antonio
The paper introduces the problem of reducing impact of freight service trips in urban areas and presents the main design objectives, requirements, and steps of a new fully electric vehicle able to autonomously load and unload palletised or boxed freights. The subject is described under a multidisciplinary point of view integrating the mechatronic design, the efficient power supply system, the intelligent mobility control modules, the strategy for freight delivery planning, through a fleet of these vehicles, based on economic and behavioural modelling.